MAN AND ENVIRONMENTAL DEGRADATION (IN AND AROUND SAMBHAR LAKE : A GEOMORPHOLIGICAL ANALYSIS) - Dr. J.K. SHARMA (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Man is a dynamic geomorphic agent which shape and reshape the surface of the earth in collaboration with environment and nature in a given area where as geomorphology is a science which deals with the form, processes and material both hard and soft of earth surface. It plays an important role in the assessment of environmental degradation of different landforms or ecosystems and their monitoring as well as management to maintain ecological balance. A diverse nature of landforms landunits exist on the surface of the earth which have been formed by the trinity principle of geomorphology specially the various processes operating on the surface of the earth over a period of millions and millions of years. The new land forms originates over the surface due to endogenetic forces at work and exogenetic forces which are mostly controlled by climatically induces elements. Man as a geomorphic agent actively shape and reshape the face of the earth by various activities like agricultural. Pastoralism, mining, lumbering as well as diversified cultural activities like settlements roads, railways, engineering structures etc.